Local Ecological Knowledge of Liberoid Coffee Farmers in Banyuwangi: an Ancestral Legacy in Preserving the Natural Environment - Danniary Ismail Faronny; Melati Julia Rahma; Wenny Bekti Sunarharum; Luchman Hakim (Universitas Diponegoro, 2024)
This study investigates the integration of Local Ecological Knowledge (LEK) in the sustainable development of Banyuwangi Liberica coffee, focusing on coffee farmers' ancestral heritage and local knowledge systems. Practices in land management, cultivation techniques, pest control, and pruning waste utilization are examined. Through qualitative data analysis from interviews and field observations, the research highlights the depth and significance of LEK in maintaining environmental sustainability and cultural heritage. Liberica coffee farmers possess a wealth of inherited LEK, encompassing ecological dynamics, sustainable agriculture, and natural resource conservation. Farmers integrate this knowledge into decision-making, evaluating innovations through research trials. Adopting appropriate practices preserves local ecosystems and maintains Liberica coffee's authenticity. The study underscores LEK's crucial role in land management and cultivation, with seedlings and repurposing waste for soil fertility. Pruning and using shade plant branches optimize fruit production and microclimate regulation. Natural pest control minimizes chemical pesticide use, preserving the coffee ecosystem's delicate balance and supporting biodiversity. Integrating LEK not only fosters environmental sustainability but also strengthens the community's social and cultural fabric. Coffee farmers' ancestral heritage and deep connection with the land contribute to the resilience of local agricultural practices, promoting the well-being of both farmers and the ecosystem.